Actualization of Islam Nusantara Values at Madrasah Qudsiyyah Kudus - Ihsan, Ihsan; Zuhri, Achmad; Annas, Azwar; Hidayati, Hanik (EDUKASIA, 2021)
This study aims to elucidate the portrait of an educational institution that actualizes Islam Nusantara values in the process of transferring knowledge to the students. This study applied a qualitative approach. Data was collected through interviews and documentation at one madrasah in Kudus City, Central Java, namely Madrasah Qudsiyyah, which is very close to local traditions and culture. This study’s results revealed that the forms of Islam Nusantara values actualization in this institution were generally depicted in the uniform as madrasah identity, teaching materials/references using Javanese, learning methods, activity essences both in routine activities and specific events, and the teachers’ productivity with their scientific specifications; thus, they give nuances that are typical of the archipelago in this madrasah.